Flowers for cancer treatment: From beauty to duty - Gutierrez-Pajares, Jorge L. (2021)
Cancer is a worldwide disease that affects millions of people every year. Although there are several approved chemotherapeutic drugs for cancer treatment, there is s constant search for new molecules. This search is supported by the need of new molecules that could target cancer cells specifically reducing side effects or that could act synergistically with approved anticancer drugs. In this review, research on flower extracts and flower-derived molecules is presented.